مقارنة مقدرات بيز لدالة المعولية لتوزيع باريتو من النوع الاول باستعمال دوال معلوماتية مضاعفة مختلفة - ناصر جنان عباس (Journal of Economics and Administrative Sciences, 2019)
The comparison of double informative priors which are assumed for the reliability function of Pareto type I distribution. To estimate the reliability function of Pareto type I distribution by using Bayes estimation, will be used two different kind of information in the Bayes estimation; two different priors have been selected for the parameter of Pareto type I distribution . Assuming distribution of three double prior’s chi- gamma squared distribution, gamma - erlang distribution, and erlang- exponential distribution as double priors. The results of the derivaties of these estimators under the squared error loss function with two different double priors. Using the simulation technique, to compare the performance for each estimator, several cases from pareto type I distribution for data generating, and for different samples sizes (small, medium, and large). It has been obtained from the simulation results the double prior distribution of gamma-erlang distribution with give a good estimation for reliability function when the true value for for all .Also the double prior distribution chi- gamma square distribution with give good estimation for reliability function when the true value for all t. And the same thing for with the values of the parameters and for all t except t=1.3. It has obtained a good estimation for reliability function (), when the double prior distribution is chi-gamma square distribution with at the true value for for all t.